Pengaruh Pembelajaran Kooperatif Think Talk Write Terhadap Kemampuan Komunikasi dan Pemecahan Masalah - Putri, Dini Palupi (Sekolah Tinggi agama Islam Negeri (STAIN) Curup, 2017)
Abstract: This research was aimed at knowing the effect of cooperative learning model type think talk write towards eight grade students abilities in mathematical communication and mathematical problem solving. The kind of this research is Quasy experiment. The population is students MTs Kerinci Regerency. Sampling technique that used in this research is random sampling. The research instrument was the written test related to students abilities in mathematical communication and mathematical problem solving. The data was analyzed with using t test and Mann-Whitney U. Result of this research showed the students abilities mathematical communication and mathematical problem solving taught by cooperative learning model think talk write was higher than the students who were taught by using conventional teaching. Cooperative Learning Think Talk Write type can be one solution to solve problems of communication ability and problem solving of student math. Keywords: Think Talk Write, Mathematical Communications, Problem Solving